Polygenic Risk for Insomnia in Adolescents of Diverse Ancestry - Ma, Tengfei; Chen, Honglei; Lu, Qing; Tong, Xiaoran (Frontiers in Genetics, 2021)
Background: Insomnia is a common mental disorder, affecting nearly one fifth of the pre-adult population in the US. The recent, largest genome wide association study conducted on the UK-Biobank cohort identified hundreds of significant single nucleotide polymorphisms, allowing the epidemiologists to quantify individual genetic predisposition in the subsequent studies via the polygenic risk scoring technique. The nucleotide polymorphisms and risk scoring, while being able to generalize to other adult populations of European origin, are not yet tested on a pediatric and adolescent population of diverse racial-ethnic backgrounds, and our study intends to fill these gaps. Material and Methods: We took the summary of the same UK-Biobank study and conducted a polygenic risk score analysis on a multi-ethnicity, pre-adult population provided by the Adolescent Brain Cognitive Development Study. Results: The polygenic risk scores according to the significant nucleotide polymorphisms found in white British adults, is a strong predictor of insomnia in children of similar European background but lacks power in non-European groups. Conclusions: Through polygenic risk scoring, the knowledge of insomnia genetics summarized from a white adult study population is transferable to a younger age group, which aids the search of actionable targets of early insomnia prevention. Yet, population stratification may prevent the easy generalization across ethnic lines, therefore, it is necessary to conduct group specific studies to aid people of non-European genetic background.